Electoral rules, political competition and fiscal expenditures: regression discontinuity evidence from Brazilian municipalities - Marcos Chamon; Jo\~ao M. P. de Mello; Sergio Firpo (Institute for the Study of Labor (IZA), 2009)
We exploit a discontinuity in Brazilian municipal election rules to investigate whether political competition has a causal impact on policy choices. In municipalities with less than 200,000 voters mayors are elected with a plurality of the vote. In municipalities with more than 200,000 voters a runoff election takes place among the top two candidates if neither achieves a majority of the votes. We show that the possibility of runoff increases political competition. We use the discontinuity as a source of exogenous variation to infer causality from political competition to fiscal policy. Our results suggest that political competition induces more investment and less current expenditures, particularly personnel expenditures. The impact of political competition is larger when incumbents can run for reelection, suggesting incentives matter insofar as incumbents can themselves remain in office.
Keywords: H72; D72; C14; P1; 330; Electoral systems; political competition; regression discontinuity; fiscal expenditures; Kommunale Finanzpolitik; Public Choice; Kommunalwahl; Wahlsystem; Schätzung; Brasilien